2022
DOI: 10.1021/acs.analchem.1c05470
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive, Topical Sampling of Potential, Low-Molecular Weight, Skin Cancer Biomarkers: A Study on Healthy Volunteers

Abstract: Monitoring of low-molecular weight cancer biomarkers, such as tryptophan (Trp) and its derivative kynurenine (Kyn), might be advantageous to non-invasive skin cancer detection. Thus, we assessed several approaches of topical sampling of Trp and Kyn, in relation to phenylalanine (Phe) and tyrosine (Tyr), on the volar forearm of six healthy volunteers. The sampling was performed with three hydrogels (made of agarose or/and chitosan), hydrated starch films, cotton swabs, and tape stripping. The biomarkers were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…To investigate the detection performance of the ten‐layer (10L) D‐nanomembrane, we analyzed the L‐Kyn level using serum and cerebro‐spinal fluid (CSF) ( n =7) clinical human samples from patients with Alzheimer's disease (AD) and healthy subjects. The concentrations of L‐Kyn in the serum was 1.01±0.27 μM in healthy subjects and 1.56±0.45 μM from patients with Alzheimer's disease, respectively, while the L‐Kyn levels in the CSF for these two groups were 0.12±0.053 μM and 0.17±0.045 μM (Figures 5c and 5d), respectively, as confirmed by liquid chromatography with tandem mass spectrometry (LC/MS/MS) (Tables S5 and S6) [32] . Notably, the sensitivity was approximately two orders of magnitude superior than that of LC/MS/MS (Figure S22), thus, providing capability to monitor Kyn in clinical samples.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…To investigate the detection performance of the ten‐layer (10L) D‐nanomembrane, we analyzed the L‐Kyn level using serum and cerebro‐spinal fluid (CSF) ( n =7) clinical human samples from patients with Alzheimer's disease (AD) and healthy subjects. The concentrations of L‐Kyn in the serum was 1.01±0.27 μM in healthy subjects and 1.56±0.45 μM from patients with Alzheimer's disease, respectively, while the L‐Kyn levels in the CSF for these two groups were 0.12±0.053 μM and 0.17±0.045 μM (Figures 5c and 5d), respectively, as confirmed by liquid chromatography with tandem mass spectrometry (LC/MS/MS) (Tables S5 and S6) [32] . Notably, the sensitivity was approximately two orders of magnitude superior than that of LC/MS/MS (Figure S22), thus, providing capability to monitor Kyn in clinical samples.…”
Section: Resultsmentioning
confidence: 66%
“…Analysis showed that the ionic current decreased from 39.53±1.43 nA to 4.51±1.87 nA as the concentration of L‐Kyn increased from 10 −8 mM to 10 −1 mM in a linear fashion when using the 10L D‐Se nanomembrane while the ionic current decreased from 39.53 nA±1.43 nA to 38.98±1.65 nA as the concentration of D‐Kyn increased from 10 −8 mM to 10 −1 mM using the 10L D‐Se nanomembrane (Figures 4d and 4e). The linear calibration curve between Kyn concentration and the intensity of the photo‐driven ion current signal was established for the detection of L‐Kyn, with a limit of detection (LOD) of 0.0074 nM for L‐Kyn when using the 10L D‐Se nanomembrane (Figure 4f), with better levels of sensitivity that were ten‐fold higher than previously reported methods (Table S3) [32] . In addition, an LOD of 0.0058 nM for D‐Kyn was achieved by the L‐nanomembrane (Figure S18).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Noninvasive sampling offers easy access to physiologically relevant biomarkers with minimum discomfort and supervision . Sweat, tear fluid, saliva, urine, breath, stool, seminal fluid, and swab specimen are the dominant sample types that can be collected noninvasively and analyzed using integrated diagnostic devices. , The analytical instruments used in current scientific studies, such as ion chromatography, electrophoresis, atomic spectroscopy, and mass spectroscopy, are often subject to stringent operating guidelines, delicate sample preparation, and meticulous maintenance. However, these analyses are currently only available in centralized laboratories.…”
Section: Introductionmentioning
confidence: 99%